Evaluating the success factors of integrating the railway into the public urban–suburban transport - Šimunović, Ljupko; Hirnig, Saša; Abramović, Borna (Transport, 2023)
The success of integrating the railway into the public urban and suburban transport depends upon a range of internal and external factors, with challenges arising in their number and complex interdependence. Furthermore, the significance and impact of some factors are uneven in cities. There is a necessity for the right mix of different factors that drive significant use of railway into the Public Transport System (PTS). The research problem is finding and defining factors needed to assess the success of railway implementation into public urban and suburban transport. An efficiency analysis of the factors that impact the level of the planned transport system use was conducted in a hierarchical or network system. The 1st step of research is to the determination of relevant factors. In this research 27 factors were determined. Based on the determining factors and their connection it is possible to design an Analytic Network Process (ANP) to evaluate the importance of factors. Factors are divided into 4 clusters: (1) user features, (2) road transport features, (3) services features, and (4) city and corridor features. Testing was carried out by group decision-making process by members of an expert panel. According to the testing, the most important factors according to their weight are: (1) frequency with 0.11651, (2) employment level with 0.10146, (3) ticket price with 0.09714, (4) reliability with 0.07256, and (5) integration of services with 0,07065. Using the weight of each factor it is possible to evaluate the success likelihood of a concrete project. In this research case study was oriented on integrating the railway into the public urban and suburban transport in the City of Rijeka in Croatia. For this purpose, the relevance of the determined weight factors was used for the concrete project of integration in the City of Rijeka that resulting in 67.17% fulfilment of the successful integration railway into the public urban and suburban transport.